2011
DOI: 10.1007/s11738-011-0809-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling during salt stress of young cotton (Gossypium hirsutum) seedlings via Solexa sequencing

Abstract: Genome-wide gene expression profiling was conducted by Solexa sequencing in order to gain insight into the transcriptome dynamics that are associated with salt stress of cotton seedlings. A total of 145,794 and 138,518 clean tags were generated from the control and salinity libraries, respectively. Of these, 75,500 (51.8%) and 72,077 (52.0%) tags were matched to the reference genes. The most differentially regulated tags with a log2ratio [2 or [-2 (P \ 0.001) were analyzed further, representing 125 up-and 171 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…RT-PCR results basically confirmed the reliability of our transcriptome analysis. However, the two techniques essentially use different algorithms, which may explain the above-mentioned some inconsistent results [49][51].…”
Section: Resultsmentioning
confidence: 99%
“…RT-PCR results basically confirmed the reliability of our transcriptome analysis. However, the two techniques essentially use different algorithms, which may explain the above-mentioned some inconsistent results [49][51].…”
Section: Resultsmentioning
confidence: 99%
“…confirmed that carbohydrate metabolic processes, hydrolase activity and catalytic activity items contained some of the identified salt-responsive transcripts. Studies with the transcriptome of Gossypium hirsutum seedlings under salt stress also reported that most enriched categories referred to metabolism and signalling pathways, among others [67]. From the KEGG enrichment analysis, pathways involved in amino sugar and nucleotide sugar metabolism; plant hormone signal transduction; alanine, aspartate and glutamate metabolism; and alpha-linolenic acid metabolism, among others, were up-regulated, whereas those involved in starch and sucrose metabolism and phenylpropanoid biosynthesis, among others, were down-regulated under salt stress.…”
Section: Discussionmentioning
confidence: 97%
“…(Col-0) seeds were surface sterilized and placed on Murashige and Skoog (MS) semisolid agar plates (with 1% sucrose, 1.5% agar, pH 6.8) 40 in a growth chamber at 16 h light (150 μE m -2 s -1 , 20°C, 60% relative humidity)/8 h dark (16°C, 75% relative humidity) cycle. Uniformly developed 16-d-old seedlings from plates were transferred into liquid medium, 41 and kept on a rotary shaker (100 rpm, continuous light) for 20 h at 22°C. Thereafter, NaCl (150 mM final concentration) was added to the medium.…”
Section: Methodsmentioning
confidence: 99%